الأداء الوظيفي بالقيم الإسلامية (قيمة التعاون والتكامل) ودورها في تعزيز الرضا الوظيفي للموارد البشرية: Functional Performance in Islamic Values (Value of Cooperation and Integration) and Its Role in Promoting Job Satisfaction for Human Resources - Hakima, Merazga; Sarif, Suhaili; Achour, Meguellatti (Online Journal of Research in Islamic Studies, 2020)
In light of the increasing challenges, organizations are directing their efforts to achieve outstanding performance. Considering that an effective human resource created and imbued with Islamic values ​​(value of cooperation and integration) that regulates its behavior when performing its tasks is a real guarantee to reach job satisfaction and then achieve performance. It controls the organization in a holistic manner, guides and ensures its success. This comes to functional research to answer the following question: What is the role of the functionality of Islamic values ​​(the value of cooperation and integration) in promoting job satisfaction and human resources?